A life cycle assessment and economic analysis of the Scum-to-Biodiesel technology in wastewater treatment plants. (March 2016) - Mu, Dongyan; Addy, Min; Anderson, Erik; Chen, Paul; Ruan, Roger
Highlights: Firstly examined the scum conversion technologies environmentally and economically. The Scum-to-Biodiesel technology has significant environmental benefits. The Scum-to-Biodiesel makes higher revenue than other conversion technologies. Abstract: This study used life cycle assessment and technical economic analysis tools in evaluating a novel Scum-to-Biodiesel technology and compares the technology with scum digestion and combustion processes. The key variables that control environmental and economic performance are identified and discussed. The results show that all impacts examined for the Scum-to-Biodiesel technology are below zero indicating significant environmental benefits could be drawn from it. Of the three technologies examined, the Scum-to-Biodiesel technology has the best environmental performance in fossil fuel depletion, GHG emissions, and eutrophication, whereas combustion has the best performance on acidification. Of all process inputs assessed, process heat, glycerol, and methanol uses had the highest impacts, much more than any other inputs considered. The Scum-to-Biodiesel technology also makes higher revenue than other technologies. The diesel price is a key variable for its economic performance. The research demonstrates the feasibility and benefits in developing Scum-to-Biodiesel technology in wastewater treatment facilities.